Managing Exercise-Induced Bronchoconstriction: A Comprehensive Review of Strategies for Athletes to Maintain Fitness and Health - Genta Dwi Putra; Arsil Arsil; Tjung Hauw Sin; Ardo Okilanda; Dally Rahman; Yovhandra Ockta (Postgraduate, University of Mataram, 2024)
Exercise-induced bronchoconstriction (EIB) significantly impacts athletes by impairing their performance and overall health. Characterized by airway narrowing during or after physical activity, EIB affects the quality of training and competition. This study employs a qualitative descriptive research model based on a comprehensive literature review to evaluate EIB management strategies in athletes. We systematically collected data from trusted scientific databases—Scopus, Science Direct, and Google Scholar—using keywords such as